Preliminary discussion on the current status of city marathons in China - Kang, Seo-hyeon; Cho, Jung-seok (Cambridge Sport Science, 2025)
In recent years, city marathons in China have shown a significant upward trend, spreading across the country. The more recognized city marathons are, the more they reflect their endless charm and powerful functions. By consulting a large amount of literature, conducting discussions with numerous marathon experts and participants, and visiting marathon events on site in various locations, the author has concluded that in addition to the often-mentioned role as a city's calling card, there are many "functions" that organizers need to explore and many details that require improvement. Furthermore, city marathons have become a necessary choice for people to alleviate life pressures, reduce status anxiety, and achieve a strong physique, a perfect personality, and a healthy lifestyle.